A Faithful Braid Group Action on the Stable Category of Tricomplexes - Khovanov, Mikhail; Qi, You (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
Bicomplexes of vector spaces frequently appear throughout algebra and geometry. In Section 2, we explain how to think about the arrows in the spectral sequence of a bicomplex via its indecomposable summands. Polycomplexes seem to be much rarer. In Section 3 of this paper, we rethink a well-known faithful categorical braid group action via an action on the stable category of tricomplexes.